2021
DOI: 10.3390/s21165658
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Based Fault Detection Model for Optimization of Shipping Operations and Enhancement of Maritime Safety

Abstract: The ability to exploit data for obtaining useful and actionable information and for providing insights is an essential element for continuous process improvements. Recognizing the value of data as an asset, marine engineering puts data considerations at the core of system design. Used wisely, data can help the shipping sector to achieve operating cost savings and efficiency increase, higher safety, wellness of crew rates, and enhanced environmental protection and security of assets. The main goal of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…There are different approaches [17,18] to realize the maintenance procedures based on the actual state of the ladle cars. For instance, in paper [19], the applicability of 1D-CNN models in performing condition monitoring in ships was noted. In paper [20], a system with infrared control for diagnosing the state of ladle bricks is proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are different approaches [17,18] to realize the maintenance procedures based on the actual state of the ladle cars. For instance, in paper [19], the applicability of 1D-CNN models in performing condition monitoring in ships was noted. In paper [20], a system with infrared control for diagnosing the state of ladle bricks is proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Benedetti et al [12] proposed an anomaly detection approach detecting anomalies in photovoltaic systems based on artificial neural networks to generate predictive maintenance alerts. Furthermore, Theodoropoulos et al [30] evaluated Deep Learning-based approaches in a maritime industry sustainability. The work [30] showed that 1D-CNN models can successfully deduce important properties, i.e., component decay and status, in different time horizons.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…CNNs are particularly useful for finding patterns in images to recognize objects, faces, and scenes. They can also be quite effective for classifying non-image data such as audio, time series, and signal data [64][65][66][67][68][69][70][71][72][73]. Figure 9 shows an example of image classification using a CNN [65].…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%